2011
DOI: 10.4028/www.scientific.net/amr.188.203
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Surface Roughness with Mill-Grinding SiC Particle Reinforced Aluminum Matrix Composites

Abstract: In view of the present machining status of SiC particle reinforced aluminum matrix composites, the electroplated diamond wheel (80# diamond grit) was used for mill-grinding the SiC particle reinforced aluminum matrix composites and the effect of speed ratio (q) and material removal rate (MRR) on surface roughness was studied based on experiments. The experimental results show that surface roughness almost increases with the increase of speed ratio. At the same material removal rate, surface roughness increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Yao et al [207] recommended a resin-based diamond grinding wheel for 45% (volume fraction) SiC p /Al composites to achieve the best SR, whereas Li et al [208] suggested HSS with a super-hard abrasive layer (diamond abrasive and binding agent) to increase the MRR. It is believed that appropriately increasing the feed rate and decreasing the millgrinding depth can obtain less SR [209]. For ductile-regime grinding, Huang et al [213] revealed that the critical grinding depth of ductile-regime machining of SiC p /Al composites decreased with increasing volume fraction of SiC particles due to the decrease in the supporting function of the Al alloy matrix.…”
Section: Mill Grinding Cylindrical Grinding and Ductileregime Grindingmentioning
confidence: 99%
“…Yao et al [207] recommended a resin-based diamond grinding wheel for 45% (volume fraction) SiC p /Al composites to achieve the best SR, whereas Li et al [208] suggested HSS with a super-hard abrasive layer (diamond abrasive and binding agent) to increase the MRR. It is believed that appropriately increasing the feed rate and decreasing the millgrinding depth can obtain less SR [209]. For ductile-regime grinding, Huang et al [213] revealed that the critical grinding depth of ductile-regime machining of SiC p /Al composites decreased with increasing volume fraction of SiC particles due to the decrease in the supporting function of the Al alloy matrix.…”
Section: Mill Grinding Cylindrical Grinding and Ductileregime Grindingmentioning
confidence: 99%
“…The results also agreed with those in other processes, such as grinding of CFRP, steel-ceramic composites, and ceramic matrix composites, and RUM of CFRP, Ti, ceramics, and so on. 7,50,[54][55][56][57][58][59][60] The possible reason for R a and its variation changes was that by equations (1) and (2), the increase in abrasive size (abrasive-grain diameter) caused the decrease in the number of active grains participating in machining on both the outside and end faces. And then it caused the decrease in the total cutting contact resulting in the increase in surface roughness.…”
Section: Effects On Surface Roughnessmentioning
confidence: 99%
“…For this reason, the two-slot tool led to a smaller surface roughness than that without slots. 50,59,60 Comparing with the two-slot tool, the four-slot tool had less abrasive grains taking part in grinding, resulting in the decrease in active cutting contact (time and area) and further leading to a larger R a value. 50 In addition, the decreasing rate of the number of grains was much larger, resulting in the increase in average MRR (MRR 1 ) and further the increase in tool wear, which led to the increase in surface roughness.…”
Section: Effects On Surface Roughnessmentioning
confidence: 99%
“…For example, Yao et al investigated experimentally the mill-grinding process of SiC particle reinforced aluminum matrix composites from the view point of materials removal rate, while Li et al studied it in terms of the surface roughness. 4,5 Kwak and Kim developed the models for predicting the grinding force and the surface roughness of the aluminum matrix composites reinforced with SiC particles. 6 Zhong and Hung found that the ductile streaks was formed on the Al 2 O 3 particles and the SiC particles during grinding the aluminum matrix composites using a 3000-grit diamond wheel with depths of cut of 1.0 and 0.5 lm.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Some effective measures were accordingly put forward in order to improve the grindability and control the surface integrity. For example, Yao et al investigated experimentally the mill-grinding process of SiC particle reinforced aluminum matrix composites from the view point of materials removal rate, while Li et al studied it in terms of the surface roughness.…”
Section: Introductionmentioning
confidence: 99%